Coliform Bacteria Contaminations in the Production of Drinking Water and Ice in the Health Region 13, 2006 - Silawan, Surachai; Sajjawattana, Tanadej; Promhirankul, Prapapan; Teerasmite, Karuna; Sittiopakul, Somchai; Chamchuglin, Somchai; Kengkhuntot, Bumpen (Journal of Health Science of Thailand, 2017)
This research was aimed to determine the contaminations of coliform bacteria and factors contributing to the contaminations regarding environment conditions and workersี behaviors in drinking water and ice production based on GMP standard. Thirty two samples out of eighty two factories with reported bacterial contaminations in 2005 were sampled by simple random sampling,in which twenty one of them were producing drinking water and eleven ice producing factories. Samples of water and ice were collected every step of production process to determine coliform bacteria contaminations using test kits of the Health Department, Ministry of Public Health. Interview and observation on workersี activities and environmental condition were conducted. Data were analyzed using rate, ratio, and proportion. As a result, bacterial contaminations were reported in every step of production process in 21.87 percent of the samples mostly in holding tanks of chlorinated waters (45%), chemical or physical filtrations (59.26%) and bottling process (63.16%). The contaminations were even reported in finished products both in small (95.24%) and large bottles (94.74%). Contaminations of waters (85.71%) used in bottle cleaning were reported. Failures may be due to incomplete disinfection plus irregular examination of residual chlorine, infrequent back-washing, contaminated waters in bottle cleaning, unhygienic processing areas/working procedures and unsteriled clothings.